Kontribusi Perempuan Pengusaha Sagu Lempeng Terhadap Pendapatan Rumah Tangga (Studi Kasus pada Ibu-Ibu Bakar Sagu di Desa Luhu Kecamatan Huamual Kabupaten Seram Bagian Barat) - Ikro, Linda P; Sopamena, Junianti F; Luhukay, Johanna M (Universitas Pattimura, 2025)
This study aims to determine the extent to which the sago plate processing business operated by women contributes to family income and how the income is utilized in Luhu Village, Huamual District, West Seram Regency. The research employs a descriptive quantitative approach with purposive sampling, involving 38 female entrepreneurs selected through a census method. The analysis technique used is family income analysis. The results show that the average monthly income earned by housewives from the sago plate business is IDR 3,142,256, while the average monthly income of their husbands is IDR 2,640,970, representing 54% and 46% of total family income, respectively. These findings indicate that the sago plate business significantly contributes to household welfare by supporting daily consumption needs and children's education. Thus, the income generated from this business plays an essential role in improving the economic resilience of families in Luhu Village.